Characterization of airborne dust samples collected from core areas of Kathmandu Valley. Issue 4 (April 2020) - Neupane, Bhanu B.; Sharma, Amita; Giri, Basant; Joshi, Mahesh K.
Abstract: Kathmandu Valley is reported to be one of the highly polluted and populated cities in the world. Particulate matter is one of the major contributors of unhealthy air in Kathmandu. Although there are several reports on spatial and temporal variation of air quality of Kathmandu Valley, the morphological and mineralogical characteristics of particulate matter are very limited or none. In this study, we report on the mineralogical and morphological analysis of airborne particulate matter collected from densely populated core areas of Kathmandu Valley using spectroscopic and microscopic techniques. The Fourier Transform Infrared (FTIR) and X-ray Diffraction (XRD) data showed the presence of clay minerals, crystalline silicate mineral, carbonate minerals, and asbestiform mineral in the dust samples. The field emission scanning electron microscopic analysis confirmed the existence of particles having diverse morphology with some of the particles having aspect ratio as high as twenty; indicating the existence of asbestiform type minerals. Based on SEM-EDX data, we found that the relative distribution of elements to be different in different samples and C, O, Mg, Ca, and Si were the major elements in the dust samples. Interestingly, the XRD data analysis showed that in all the samples quartz mineral having high degree of crystallinity was present. The XRD measurement was also carried out in three different brands of cement samples. Few minerals present in dust samples were also identified in the cement samples. This observation could indicate that cement is one of the sources of minerals in the airborne particulate matter in the Kathmandu Valley. Abstract : Particulate matter; Clay minerals; Asbestos; Cement; Microscopy materials science; Chemistry; Environmental science; Earth sciences; Health sciences.